Developing circular accounting for carbon emissions measurement in Indonesia: a literature review - Indriani, Ika Kurnia; Kurniasih, Ninik; Soraya, Soraya (Nur Science Institute, 2025)
This study aims to develop carbon footprint measurements using attribution and consequential methods. Attribution and consequential methods have been widely implemented in Europe and America. Carbon emission sources are classified based on consumption and production activity categories. However, in Indonesia, forest and land fires are the highest source of carbon emissions, occurring almost every year during the dry season in peatlands. Peatland exploitation leads to forest fires and deforestation of tropical forests in Indonesia. The impacts of these fires include the loss of ecosystem benefits and biodiversity. Peatlands in Indonesia are estimated to produce 68.6 gigatons of carbon, equivalent to 10% to 14% of the world's organic carbon sources. Accounting methods can be used to measure and report carbon emissions caused by forest and land fires. This study used a systematic literature review. The literature used comes from carbon accounting experts in the UK, published in Scopus-indexed journals. The study results show that attribution and consequential methods could be used to measure the carbon footprint caused by peatland exploitation. The Indonesian government could adopt this method in developing circular accounting for carbon emission measurement and reporting.